Episodic Uplift along a Quaternary Fault, A Signature of Active Deformation in Frontal Part of Karachi Arc, Southern Pakistan - Ahmad Nabi; Xiaodong Liu; Zhijun Gong; Khalid Pervaiz; Abbas Ali; Shahbaz Ashraf (International Journal of Economic and Environmental Geology, 2018)
The southern part of Kirthar Fold Belt represents a divergent wrench regime marked by open arcuate structures, collectively called as Karachi Arc. The frontal part of Karachi Arc is being actively deformed. The active deformation is manifested by the neotectonic features recorded in the recent sediments. Frontal part of northern Karachi Arc has been investigated to locate Earthquake Environmental Effects (EEE) in Bizan Dhoro area northwest of Hyderabad. A linear structure in Bizan Dhoro area at frontal part of northern Karachi Arc has been investigated. The structure was interpreted in front of Laki Range with the help of LANDSAT ETM and SPOT Images. The lineament on ground is represented by a NNW oriented linear topographic step in the peneplain alluvial fans. The frontal peneplain of Laki Range is constituted by the alluvial fans composed of clast supported gravel ranging from pebble-to-boulder in size laid down by Bizan Dhoro and its tributaries. Four new generations of alluvial fans have been recognized across the lineament which suggests that the area has experienced at least three episodes of uplift along the topographic step named as Bizan Dhoro Fault. Electric resistivity tomography across Bizan Dhoro fault and evidences of tectonic geomorphology revealed that it is a capable reverse fault dipping at an angle of 60° towards west which has experienced at least three events after deposition of Quaternary alluvial fans. No brittle deformation however could be recorded in the gravels. Bizan Dhoro fault is an embryonic structure that depicts active deformation of foreland parallel to the fold and thrust belt.